2023
DOI: 10.1002/ece3.10483
|View full text |Cite
|
Sign up to set email alerts
|

Physiology of the widespread pulsating soft coralXenia umbellatais affected by food sources, but not by water flow

C. E. L. Hill,
S. G. Abbass,
G. Caporale
et al.

Abstract: Coral energy and nutrient acquisition strategies are complex and sensitive to environmental conditions such as water flow. While high water flow can enhance feeding in hard corals, knowledge about the effects of water flow on the feeding of soft corals, particularly those pulsating, is still limited. In this study, we thus investigated the effects of feeding and water flow on the physiology of the pulsating soft coral Xenia umbellata. We crossed three feeding treatments: (i) no feeding, (ii) particulate organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…Previous studies have reported reductions of Xenia spp. pulsation rates in response to warming [39], heavy nitrate eutrophication [38], a lack of a heterotrophic food source [41], and exposure to oil dispersants [40]. The synchronous opening and contracting of the polyp tentacles, in a continuous rhythm, results in a water flow that enhances photosynthesis by rapidly removing excess oxygen while increasing CO 2 affinity of ribulose-1,5-bisphosphate carboxylase oxygenase (RuBisCO) and preventing refiltration of surrounding water by neighboring polyps [36,37,58].…”
Section: Acidification Affected Pulsation and Growth Of X Umbellatamentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported reductions of Xenia spp. pulsation rates in response to warming [39], heavy nitrate eutrophication [38], a lack of a heterotrophic food source [41], and exposure to oil dispersants [40]. The synchronous opening and contracting of the polyp tentacles, in a continuous rhythm, results in a water flow that enhances photosynthesis by rapidly removing excess oxygen while increasing CO 2 affinity of ribulose-1,5-bisphosphate carboxylase oxygenase (RuBisCO) and preventing refiltration of surrounding water by neighboring polyps [36,37,58].…”
Section: Acidification Affected Pulsation and Growth Of X Umbellatamentioning
confidence: 99%
“…Xenia umbellata has been subject to experiments assessing the (combined) effects of global and/or local factors; e.g., dissolved organic C eutrophication and warming [39,74,75], nitrate eutrophication and warming [38], phosphate eutrophication and warming [53,76], water flow and food availability [41], and in-situ eutrophication [54,77]. Future scenarios for corals will likely include multiple global and local factors, with ocean warming as the most urgent threat.…”
Section: Ecological Implicationsmentioning
confidence: 99%
See 1 more Smart Citation